2002
DOI: 10.1097/00007632-200201010-00026
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Excision of Hemivertebrae Via the Posterior Approach Alone for Congenital Spine Deformity

Abstract: The described procedure was less invasive because it avoided an anterior approach, yet it yielded satisfactory long-term results for thoracolumbar hemivertebrae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 14 publications
9
66
0
5
Order By: Relevance
“…Recently, Leatherman and Dickson [22] popularized it again. In many subsequent studies, it has been reported that complete excision of hemivertebra at the same session at one or two steps leads to pronounced improvement as well as spontaneous correction [4,7,10,19]. Bradford and Boachie-Adjei reported a 70% correction in Cobb angle.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Leatherman and Dickson [22] popularized it again. In many subsequent studies, it has been reported that complete excision of hemivertebra at the same session at one or two steps leads to pronounced improvement as well as spontaneous correction [4,7,10,19]. Bradford and Boachie-Adjei reported a 70% correction in Cobb angle.…”
Section: Discussionmentioning
confidence: 96%
“…This can be done by correctional cast braces. Filling and closing of the space by compression is easier with instrumentation applications [1,5,10]. On the other hand, instrumentation in children brings about the problems of finding suitable pediatric instruments, subcutaneous protuberance of the instruments, difficulty in wound closure, wound healing problems, and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correction rate of scoliosis is reported from 35.2% to 70% 4-6,9-12,23 , whereas correction rate of kyphosis is from 54.2% to 67.4% [9][10][11][12] . Our cases were in no way inferior to these reports which showed 36.8% and 55.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Hemivertebral resections using a single posterior approach has the advantage of less surgical impact; however, the procedure carries risk, including neurovascular injury and insufficient osteotomy. To solve these problems, since 2003 we have attempted hemivertebra resections using single-stage surgery via a posterior approach alone, utilizing CT-based navigation system.…”
mentioning
confidence: 99%